ECOLOGY OF THE BLUE CRAB PORTUNUS PELAGICUS (LINNAEUS) AND ITS POTENTIAL FISHERY IN ZUARI ESTUARY - Dhawan, Rajinder M; Dwivedi, S N; Rajamanickam, G Victor (Indian Journal of Fisheries, 2011)
The occurrence of the tblue cra'b Portill/IIS peiagicils was studied fromDecember 1972 to April 1973 in Zuari estuary. Environmerital parameters, 'liz.,temperature, saHnity, oxygen, light penetpation and nature of bottom wer~ also9tudied. 4519 Crabs were caught in 26 trawls; the males were 67.54% and thefemales were 32.46%. The dominant size groups for males 'and females were115 mm and 105 mm, respectively. Females mature at a smaller size and breedingMkes place during February-March. The widthlweight reitationship study show,~dthat females were heavier. The 'regression equation for female is:weight = 4.233 x 10-9 x L 4.969, and for male is:we:ght = 2.750 x 10-6 x L 3,636. The crabs were found to prefer loamy soil.The crab Portlll1l1S pefagiclIs constitutes a good food resource in the moutl>, regionof Zuari estuary.